PEMBELAJARAN PEMAHAMAN KONSEP IPA SISWA KELAS III SD PADA MATERI WUJUD BENDA DENGAN MENGGUNAKAN METODE DEMONSTRASI - Maya Fitria; Jajang Bayu Kelana (IKIP Siliwangi, 2020)
This study aims to examine the learning of natural science concept understanding in material objects of third grade elementary school students using demonstration methods. The research method used is descriptive qualitative. The subjects in this study were students of class III SDN Girimulya with a total of 32 students consisting of 15 male students and 17 female students. The instruments used were teacher and student observation sheets, questions about understanding the concept of science, as well as teacher and student questionnaires. The results showed that there was an increase in the quality of learning when the demonstration method was applied. This is indicated by the average score on teacher observations of 88, the average score on student observations of 87, the percentage increase from the Pre-Test to Post-Test scores of 6.66%, and the percentage of the teacher's questionnaire score of 80%, and the average percentage of students' questionnaire scores was 80%.